Synthesis of 2-substituted 4(R)-hydroxy-2-cyclopenten-1-one, a prostaglandin intermediate with methyl oleate from palm oil - Omar, Muhammad Nor; Hamilton, Richard J. (Malaysian Palm Oil Board, 2004)

(untitled)
Methyl oleate, 1 was obtained from palm methyl esters through removal of saturated esters in a urea complex formation followed by silver nitrate impregnated silica gel column chromatography. The oleate was then reacted with 2,3-O-isopropylidene-D-glyceraldehyde 2, to form an aldol compound which, after lactonization, formation of tosylate and cyclic cyanohydrin, and oxidation of the double bond afforded 2-(6-carbomethoxyhexyl)-4(R)-hydroxy-2-cyclopenten-1-one 11, a prostaglandin intermediate.